The Influence of Realia Media on Increasing Students' Logical Intelligence in Mathematics Learning at MI Muhammadiyah Ngadirejan - Safitri Anita; Ruhardi Rudi; Agustiani Happy (Journal of Education Technology and Inovation, 2024)
This study aims to determine the influence of realia media in increasing students' logical intelligence in mathematics learning. The type of research used is descriptive quantitative. The sample used amounted to 40 students including grade III and IV students of MI Muhammadiyah Ngadirejan using purposive sample techniques. Some of the instruments used to collect data include questionnaires, observations, and documentation. Data analysis using prerequisite tests, simple linear regression tests, and t-tests. From the results of the study, the results of a simple linear regression test sig = 0.000 can be interpreted as a significant influence. The results of the analysis used the significance test t count (4.595) ? t table (1.685). Therefore, we can confirm that the use of Realia media plays an important role in the development of logical thinking of MI Muhammadiyah Ngadirejan III and IV grade students